Initial Experience With Gallium-68 DOTA-Octreotate PET/CT and Peptide Receptor Radionuclide Therapy for Pediatric Patients With Refractory Metastatic Neuroblastoma. Issue 2 (March 2016) - Kong, Grace; Hofman, Michael S.; Murray, William K.; Wilson, Sharyn; Wood, Paul; Downie, Peter; Super, Leanne; Hogg, Annette; Eu, Peter; Hicks, Rodney J.
Abstract : Rationale: Pediatric patients with refractory neuroblastoma have limited therapeutic options. Neuroblastoma may express somatostatin receptors (SSTRs) allowing imaging with 68 Ga-DOTA-Octreotate (GaTATE) positron emission tomography/computed tomography (PET/CT) and peptide receptor radionuclide therapy (PRRT). We reviewed our experience with this theranostic combination. Materials and Methods: GaTATE studies (8 patients; 2 to 9 years old) were reviewed and compared with 123 I-MIBG or posttreatment 131 I-MIBG studies. Immunohistochemistry (IHC) for SSTR subtype 2 was performed in 5 patients. Four patients received PRRT. Results: GaTATE PET showed additional disease in 38% (3/8 patients), and upstaged 1 patient by detecting marrow involvement. IHC detected SSTR 2 in all patients assessed. Six patients were deemed suitable for PRRT on imaging. Four patients received 17 cycles of palliative PRRT (10 111 In-DOTATATE; 5 177 Lu-DOTATATE; 1 combined 111 In and 177 Lu-DOTATATE; 1 combined 177 Lu and 90 Y-DOTATATE) with no significant toxicity attributed to PRRT. All had objective responses. Two survivors are now 40 and 56 months from PRRT commencement. Conclusions: GaTATE PET was positive in a high proportion of patients with refractory neuroblastoma, correlating with SSTR 2 on IHC, with additional disease identified compared with MIBG imaging. PRRT seems safe, feasible, with responses observed in patients with progression despite multimodality treatment. These data support ongoing clinical trials in such patients.